The Professionalism Competency of Islamic Cultural History Teachers in Classroom Management - Junaidi Arsyad (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the professional competence of Islamic cultural history teachers in managing the class during the teaching and learning process. The participants in this study were the Deputy Head of the Madrasah for Curriculum, 2 Islamic Cultural History teachers and two students. This study uses primary data and secondary data as data sources. While the data collection tools are through interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. In order to assess the credibility of the data, it is important to employ several techniques such as prolonging the duration of observation, employing triangulation, exercising meticulous observation, and conducting member checks. These measures ensure that the information acquired can be effectively utilised in research, aligning with the intended meaning conveyed by the informant. The findings of the study indicate that class management strategies were used in two separate manners. Specifically, one teacher of Islamic Cultural History employed a technique aimed at establishing a positive atmosphere by means of ice-breaking activities, while the other teacher utilised a different ice-breaking technique. The instructor of Islamic Cultural History employs effective classroom management strategies, notably through the implementation of dynamic discussion groups characterised by enthusiastic and lively debates.